Crisis of the Neoliberal Model; Towards Regional Planning - a Polanyian Contribution - Paula Valderrama Saud (Íconos)
Using Karl Polanyi’s analytical instrument, I argue that the current withdrawal of the industrialized powers and the emergence of alternative policies in Latin America are determined by the crisis of the neoliberal model. The polarity between democracy and the market, observed since the beginnings of liberal capitalism, has deepened since the inter-war period due to the appearance of so-called “mass democracy.” Since that period, foreign policies of industrialized countries have derived from social conflict caused by this polarity. Current neoliberalism, which favors the limitation of democracy in favor of the self-regulating global market, is a system that contains inherent contradictions on financial and socio-political levels. These contradictions are the cause of the current crisis in the United States and the European Union, a crisis that favors the begin- ning of a new era characterized by greater regional planning and a plurality of development paths.